Taiwanese export trade forecasting using firefly algorithm based K-means algorithm and SVR with wavelet transform. (September 2016) - Kuo, R.J.; Li, P.S.
Highlights: Propose a model integrating wavelet transform, FA based K -means and FA based SVR. FA based K -means algorithm is employed for clustering data. FA based SVR is applied for forecasting. The results show that the proposed model outperforms other models. Abstract: In order to develop a prediction system for export trade value, this study proposes a three-stage forecasting model which integrates wavelet transform, firefly algorithm-based K -means algorithms and firefly algorithm-based support vector regression (SVR). First, wavelet transform is utilized to reduce the noise in data preprocessing. Then, the firefly algorithm-based K -means algorithm is employed for cluster analysis. Finally, a forecasting model is built for each cluster individually. For evaluation, this study compares methods with and without clustering. In addition, both non-wavelet transform and wavelet transform for data preprocessing are investigated. The experimental results indicate that the forecasting algorithm with both wavelet transform and clustering has better performance. Besides, firefly algorithm-based SVR outperforms the other algorithms.